The prevalence of hypertension and its associated risk factors among adults in rural Mandya, Karnataka, India - K. R., Ananthachari; B. R., Harish (International Journal Of Community Medicine And Public Health, 2016)
Background: Hypertension is the commonest cardiovascular disorder due to its role in the causation of coronary heart disease, stroke and other vascular complications. In India, hypertension is one of major risk factors for cardiovascular mortality and is attributed for 10% of all deaths. Increasing prevalence in hypertension is expected due to economic transition, increased population growth, ageing, behavioural risk factors such as, unhealthy diet and excessive alcohol consumption. Awareness of hypertension and risk factors for hypertension is less among rural population. Proposed study addresses the risk factors and awareness of the rural community. Methods: Cross sectional study was conducted over a period of one year from June 2013 to May 2014 among adults from randomly selected villages in the Keragodu primary health centre area. House to house survey was conducted among adults in each village and was examined for hypertension and interviewed regarding the risk factors of hypertension using a pre tested, semi structured questionnaire. Results: Among 1786 study subjects, 38.6% were males and 61.4% were females. The prevalence of hypertension was observed to be 25.9%. Prevalence increased as the age increased. The prevalence of hypertension was high among obese, those who had history of diabetes mellitus. Among the study subjects 24.1% (112) were aware of their hypertensive status, of these 56.3% were on regular treatment. Conclusions: The prevalence of hypertension was 25.9%. Various factors like increase in age, obesity, history of diabetes are implicated in the occurrence of hypertension.